2019
DOI: 10.1083/jcb.201808014
|View full text |Cite
|
Sign up to set email alerts
|

CDK1-CCNB1 creates a spindle checkpoint–permissive state by enabling MPS1 kinetochore localization

Abstract: Spindle checkpoint signaling is initiated by recruitment of the kinase MPS1 to unattached kinetochores during mitosis. We show that CDK1-CCNB1 and a counteracting phosphatase PP2A-B55 regulate the engagement of human MPS1 with unattached kinetochores by controlling the phosphorylation status of S281 in the kinetochore-binding domain. This regulation is essential for checkpoint signaling, since MPS1S281A is not recruited to unattached kinetochores and fails to support the recruitment of other checkpoint protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 86 publications
(139 reference statements)
6
90
0
Order By: Relevance
“…Specific enrichment of Cdk1 kinase activity at a particular cellular localisation could also be important. Accordingly, cyclin B is known to be recruited to the kinetochore and has recently been shown to contribute to spindle assembly checkpoint signalling by phosphorylating Mps1 . A large subset of the cyclin B‐specific substrates that we have identified using degron‐mediated depletion is indeed associated with the centromere/kinetochore, supporting the importance of this targeted localisation of cyclin B .…”
Section: Pulling the Trigger: Cdk1 Activationsupporting
confidence: 63%
“…Specific enrichment of Cdk1 kinase activity at a particular cellular localisation could also be important. Accordingly, cyclin B is known to be recruited to the kinetochore and has recently been shown to contribute to spindle assembly checkpoint signalling by phosphorylating Mps1 . A large subset of the cyclin B‐specific substrates that we have identified using degron‐mediated depletion is indeed associated with the centromere/kinetochore, supporting the importance of this targeted localisation of cyclin B .…”
Section: Pulling the Trigger: Cdk1 Activationsupporting
confidence: 63%
“…MPS1 has an N‐terminal kinetochore binding domain which associates with the NDC80/NUF2 complex at the kinetochore . It has now been shown that the N‐terminal Ser281 within the kinetochore binding domain of MPS1 has to be phosphorylated to allow efficient kinetochore recruitment of MPS1 . These data are consistent with biochemical data showing an improved binding of Ser281‐phosphorylated MPS1 to purified NDC80 complex .…”
Section: Molecular Targets Of Cdk1‐cyclin B1supporting
confidence: 81%
“…The presence or absence of CDK1 activity affects the kinetochore recruitment of all core SAC proteins implying that one or more upstream components of the SAC are regulated by CDK1 [97]. In line with this idea, it has been suggested that both localization and [169,170] activation of MPS1 are controlled by CDK1-cyclin B1 [45,98,99]. It has recently been demonstrated that phosphorylation of MPS1 by CDK1-cyclin B1 controls recruitment of MPS1 to the kinetochore in human cells [45].…”
Section: Molecular Targets Of Cdk1-cyclin B1mentioning
confidence: 94%
See 2 more Smart Citations